(untitled) (El Taco en la Brea, 2025)
Drawing on interviews and unpublished materials from his personal archive, this article investigates how Argentine writer Leopoldo Brizuela (1963-2019) elaborated his social identity throughout his life and work, reconfiguring his family histories, connecting in diverse ways with heterogeneous cultural spaces and redefining himself in terms of class, race and gender. The son of the «natural son» of a maid who worked for a wealthy family, a student at an elite Catholic school in La Plata, marked by a mandate to social climbing while devoted to anonymous folklore, Brizuela defined himself at the end of his life, with «pride», as a «negrito fino». This definition points to a different path from the one that Pierre Bourdieu and Didier Eribon postulated for the subjects of «dominated» social groups who succeed in the space of «legitimate culture». Brizuela’s challenge consisted precisely in constituting himself as a sophisticated writer and as a homosexual, and not only not distancing himself but intensifying his relationship to his imaginary place of origin.